2015
DOI: 10.1124/dmd.114.061291
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation and Deconjugation Reactions within the Fetoplacental Compartment in a Sheep Model: A Key Factor Determining Bisphenol A Fetal Exposure

Abstract: The widespread human exposure to bisphenol A (BPA), an endocrine disruptor targeting developmental processes, underlines the need to better understand the mechanisms of fetal exposure. Animal studies have shown that at a late stage of pregnancy BPA is efficiently conjugated by the fetoplacental unit, mainly into BPAglucuronide (BPA-G), which remains trapped within the fetoplacental unit. Fetal exposure to BPA-G might in turn contribute to in situ exposure to bioactive BPA, following its deconjugation into pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 52 publications
(59 reference statements)
4
26
1
2
Order By: Relevance
“…As previously mentioned, although many of these transporters show preference for sulfated conjugates, they are also capable of transporting (Gauderat et al, 2016), and to a greater extent than BPA-sulfate (Corbel et al, 2013(Corbel et al, , 2015. The authors also showed that microsomes and cytosols prepared from both fetal ewe and human livers have similar activity toward BPA glucuronidation and sulfation, respectively (Corbel et al, 2015). Taken together, it is possible that BPA-glucuronide represents a greater fraction of the conjugated BPA in the human fetal livers from this study.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…As previously mentioned, although many of these transporters show preference for sulfated conjugates, they are also capable of transporting (Gauderat et al, 2016), and to a greater extent than BPA-sulfate (Corbel et al, 2013(Corbel et al, , 2015. The authors also showed that microsomes and cytosols prepared from both fetal ewe and human livers have similar activity toward BPA glucuronidation and sulfation, respectively (Corbel et al, 2015). Taken together, it is possible that BPA-glucuronide represents a greater fraction of the conjugated BPA in the human fetal livers from this study.…”
Section: Resultssupporting
confidence: 58%
“…Interestingly, it has been shown that BPA-glucuronide is transported across the placenta to the rat fetus, where it can be deconjugated and thereby reactivated (Nishikawa et al, 2010). Similarly, it has been shown in sheep that the fetoplacental unit retains conjugated BPA metabolites (Corbel et al, 2013), creating a higher exposure of the fetus to bioactive BPA through conjugation-deconjugation cycling (Corbel et al, 2015;Gauderat et al, 2016). We have demonstrated that human fetal livers exhibit a wide range of quantifiable concentrations of both free and conjugated BPA, whereas levels in adult livers were typically below the limit of quantification (LOQ) (Nahar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although a primary site of exogenous compound detoxification in adult humans [38, 39], the liver has limited capacity to detoxify such compounds in the embryo/fetus [4042] and, as such, the developing organ is functionally challenged, in a premature state, by this myriad of toxins. The diversity of potentially toxic substances in cigarette smoke, along with multiplicity of metabolic organs that are targeted by exposure, makes it difficult to elucidate the mechanisms through which developmental exposure to cigarette smoke elicits long-lived metabolic consequences in exposed offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Although very few studies have explored the fetomaternal exchanges of EDCs, Rhind et al (2010) found no correlations between the maternal and fetal burdens at Days 55 and 110 of gestation in the livers of sheep exposed to environmentally relevant concentrations of sewage sludge. Studies on bisphenol A (BPA) in the same species show that the conjugation capabilities of the fetoplacental unit are low in early gestation (around Day 55) but higher at a later date (around Day 130), indicating that exposure to the EDC is high during the earlier developmental window (Corbel et al 2013(Corbel et al , 2015. The present review concentrates on five EDCs: BPA, octylphenol (OP), methyoxychlor (MXC), polychlorinated biphenyls (PCBs) and SS.…”
Section: Effect Of Environmental Chemicalsmentioning
confidence: 99%